2016
DOI: 10.1093/ecco-jcc/jjv241
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Golimumab Exposure: A ‘Real-Life’ Observational Study in Active Ulcerative Colitis

Abstract: Background and Aims: Golimumab has been approved recently to treat refractory moderate-tosevere ulcerative colitis [UC]. To date it is not clear why a considerable fraction of patients do not respond, or lose initial response, to golimumab therapy. Our aim was to investigate whether a low golimumab serum concentration and/or a positive anti-golimumab antibody status reduces the efficacy of this drug in patients with UC. Methods: Serum samples of 21 patients with moderate-to-severe UC were collected during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 16 publications
5
81
2
1
Order By: Relevance
“…In particular, we obtained remission in 44% of patients at the 3rd month, and only 8% of them lost the remission during the following three months. Percentage of clinical response seems to be similar to that reached in real life in referral centres [21], but lower to that obtained both in the controlled trials [11] and in a recent short-term real-life, Spanish experience [17]. It is not clear why this occurs.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…In particular, we obtained remission in 44% of patients at the 3rd month, and only 8% of them lost the remission during the following three months. Percentage of clinical response seems to be similar to that reached in real life in referral centres [21], but lower to that obtained both in the controlled trials [11] and in a recent short-term real-life, Spanish experience [17]. It is not clear why this occurs.…”
Section: Discussioncontrasting
confidence: 68%
“…Sandborn et al found that clinical response and clinical remission increased during the first 6 weeks of treatment according to serum GOL concentrations [11]. Detrez et al recently found that serum GOL concentration was significantly higher in partial clinical responders than in nonresponders, and that clinical non-responders had a significantly more severe colitis, indicated by a higher endoscopic Mayo score at baseline compared to partial clinical responders [21]. Ideally, we should measure drug levels to guide therapy and more effectively achieve the clinical response, and GOL should not escape the rule.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that these binding sites became less accessible when TNF was coated on the plate. In contrast, for the anti-TNF mAbs (e.g., golimumab), a high intraclass correlation coefficient agreement was obtained between the respective ELISA types (17). However, these anti-TNF mAbs are known to bind both monomeric and trimeric forms of TNF (16).…”
Section: Discussionmentioning
confidence: 89%
“…Detrez et al performed a prospective trial to define the therapeutic range of GLM in UC patients. A cut-off value of 2.6 lg/ml at week 6 was associated with partial clinical response at 14 weeks (defined as clinical improvement despite persistent rectal blood loss) [172]. Although efficacy for anti-TNF agents has been proven, up to 30% of patients have no clinical improvement after initiation of anti-TNF therapy (primary nonresponse), and up to 50% of patients lose response over time (secondary nonresponse) [173].…”
Section: Pharmacokinetic and Pharmacodynamic Considerationsmentioning
confidence: 99%